2006
DOI: 10.2353/ajpath.2006.050800
|View full text |Cite
|
Sign up to set email alerts
|

Glypican-1 Is Frequently Overexpressed in Human Gliomas and Enhances FGF-2 Signaling in Glioma Cells

Abstract: Signaling by fibroblast growth factor 2 (FGF-2), an autocrine stimulator of glioma growth, is regulated by heparan sulfate proteoglycans (HSPGs) via a ternary complex with FGF-2 and the FGF receptor (FGFR). To characterize glioma growth signaling, we examined whether altered HSPGs contribute to loss of growth control in gliomas. In a screen of five human glioma cell lines, U118 and U251 cell HSPGs activated FGF-2 signaling via FGFR1c. The direct comparison of U251 glioma cells with normal astrocyte HSPGs demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(149 citation statements)
references
References 45 publications
6
141
0
2
Order By: Relevance
“…In multiple myeloma high levels of shed syndecan-1 correlate with poor prognosis and have been associated with increased tumor growth in animal models [56,57]. In GBM, both total and specific HSPGs core proteins are altered (Figure 2), including increased levels of syndecan-1 and glypican-1 as previously demonstrated [23,58].…”
Section: Heparan Sulfate Proteoglycans and Extracellular Sulfatases Isupporting
confidence: 55%
“…In multiple myeloma high levels of shed syndecan-1 correlate with poor prognosis and have been associated with increased tumor growth in animal models [56,57]. In GBM, both total and specific HSPGs core proteins are altered (Figure 2), including increased levels of syndecan-1 and glypican-1 as previously demonstrated [23,58].…”
Section: Heparan Sulfate Proteoglycans and Extracellular Sulfatases Isupporting
confidence: 55%
“…For example, increased GPC1 expression in human gliomas and glioma-derived cell lines have been reported and it has been suggested that GPC1 acts by enhancing FGF basic signaling and mitogenesis (21). Similarly, GPC1 overexpression has been demonstrated in pancreatic cancer cells and it has been suggested that GPC1 plays an essential role in the response of pancreatic cancer cells to certain mitogenic stimuli, such as FGF and heparin-binding epidermal growth factor (EGF)-like growth factor (22).…”
Section: Introductionmentioning
confidence: 99%
“…There are six members of the GPC family. GPC1 is involved in tumorigenesis and angiogenesis, and is frequently overexpressed in different human malignancies including pancreatic carcinoma, breast cancer and glioma (Aikawa et al, 2008;Kleeff et al, 1998;Kleeff et al, 1999;Matsuda et al, 2001;Su et al, 2006). GPC1 has been proposed to act as a co-receptor for FGF that enhances the binding of FGF to its receptor, subsequently promoting FGF-FGFR activation and signaling (Zhang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%